Sosialisasi Dampak Gadget Bagi Anak Sekolah Dasar di SDI Mutiara Islam Al Ittiba Sangatta Utara - Nurwanaliyanti, Nurwanaliyanti; Viera, Viera; Velyna, Tri (MAYARA: Jurnal Pengabdian Masyarakat, 2025)
This Community Service Program aims to improve digital literacy and awareness of elementary school students regarding the impact of gadget use. The activity was carried out during the Field Experience Practice (PPL) at the Sangatta Islamic College on September 19, 2025, at SDI Mutiara Islam Al Ittiba, involving 85 students in grades IV–VI. The method used was an interactive lecture assisted by visual media in the form of posters and presentations, accompanied by a question and answer discussion. The material covered the benefits of gadgets, the risks of excessive use on children's health and development, and strategies for wise gadget use. The results of the activity showed an increase in students' understanding of the negative impacts of gadgets, such as impaired concentration and sleep quality, as well as awareness of the importance of limiting screen time and selecting educational content. The enthusiasm and active participation of students showed that the interactive approach was effective in improving digital literacy in elementary school-aged children. This activity is expected to become a model for strengthening school-based digital literacy through collaboration between universities and educational partners.